İlköğretim Okullarında Beden Eğitimi Dersine Yönelik Öğrenci ve Ana-Baba Tutumları - Yaldiz, Arif Serkan; Özbek, Oğuz (Kastamonu Egitim Dergisi, 2018)
The aim of this study is to determine the 6, 7 and 8 th grade primary school students’ and their parents’ attitudes towards participation in physical education courses. In this end, 717 students studying at schools in the Cankaya, Yenimahalle and Mamak Districts affiliated to Ankara Province Directorate of National Education and parents of these students, 640 in total, participated in the study voluntarily. The findings indicated that 6, 7 and 8 th grade students and their parents showed high positive attitudes towards physical education courses. However, it is concluded primary school students’ positive attitudes towards physical education courses decrease as students move through upper grade levels. No significant gender difference was found in the attitudes held by female and male parents and overall it can be said that parents have positive attitudes towards physical education courses.
Keywords: Eğitim Üzerine Çalışmalar; Tutum; Anne-Baba; Beden Eğitimi; Attitude; Parents; Physical Education; Studies on Education; 4. Education; 16. Peace & justice